Carvacrol, Thymol, and Garlic Essential Oil Promote Skin Innate Immunity in Gilthead Seabream (Sparus aurata) Through the Multifactorial Modulation of the Secretory Pathway and Enhancement of Mucus Protective Capacity - Firmino, Joana P.; Fernández-Alacid, Laura; Vallejos-Vidal, Eva; Salomón, Ricardo; Sanahuja, Ignasi; Tort, Lluis; Ibarz, Antoni; Reyes-López, Felipe E.; Gisbert, Enric (Frontiers in Immunology, 2021)
One of the main targets for the use of phytogenics in aquafeeds is the mucosal tissues as they constitute a physical and biochemical shield against environmental and pathogenic threats, comprising elements from both the innate and acquired immunity. In the present study, the modulation of the skin transcriptional immune response, the bacterial growth capacity in skin mucus, and the overall health condition of gilthead seabream (Sparus aurata) juveniles fed a dietary supplementation of garlic essential oil, carvacrol and thymol were assessed. The enrichment analysis of the skin transcriptional profile of fish fed the additive-supplemented diet revealed the regulation of genes associated to cellular components involved in the secretory pathway, suggesting the stimulation and recruitment of phagocytic cells. Genes recognized by their involvement in non-specific immune response were also identified in the analysis. The promotion of the secretion of non-specific immune molecules into the skin mucus was proposed to be involved in the in vitro decreased growth capacity of pathogenic bacteria in the mucus of fish fed the phytogenic-supplemented diet. Although the mucus antioxidant capacity was not affected by the phytogenics supplementation, the regulation of genes coding for oxidative stress enzymes suggested the reduction of the skin oxidative stress. Additionally, the decreased levels of cortisol in mucus indicated a reduction in the fish allostatic load due to the properties of the additive tested. Altogether, the dietary garlic, carvacrol and thymol appear to promote the gilthead seabream skin innate immunity and the mucus protective capacity, decreasing its susceptibility to be colonized by pathogenic bacteria.